Analisis Yuridis Penolakan Pasien Badan Penyelenggara Jaminan Sosial (BPJS) di Papua Ditinjau dari Perspektif Hak Asasi Manusia (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Abstract. The right to health is an integral part of human rights guaranteed by the Constitution and further reinforced by Law Number 17 of 2023 on Health, which places the state as the party responsible for ensuring the provision of safe, high-quality, and non-discriminatory health services for all citizens. However, in practice, the fulfillment of the right to health continues to face various challenges, particularly in the delivery of health services for participants of BPJS Kesehatan. This study aims to analyze the legal protection of the right to health in Indonesia and to examine the refusal of medical services to BPJS patients that resulted in death in Papua from a human rights perspective. The research employs a normative legal research method using statutory, conceptual, and case approaches. The findings indicate that although the national legal framework has clearly regulated the obligations of the state and health care facilities in providing emergency services, its implementation remains weak due to administrative barriers, unequal access to health services, and inconsistent law enforcement. The refusal of medical services to BPJS patients in Papua reflects a tension between hospitals’ administrative compliance and the professional obligation of medical personnel to save human lives. The implications of this study emphasize the need to strengthen supervision, ensure consistent law enforcement, and improve health service governance so that the right to health is truly protected as part of human dignity within the Indonesian rule of law.